Ductile fracture and deformation behavior in progressive microforming. (15th October 2015) - Meng, B.; Fu, M.W.; Fu, C.M.; Chen, K.S.
Graphical abstract: Highlights: Bulk microparts can be fabricated by progressive microforming of sheet metal. Undesirable strain accumulation is affected by initial grain size. Dimensional accuracy is ensured by controlling grain size and material properties. Microcrack formation can be predicted numerically by monitoring strain accumulation. Abstract: With the increasing demand for the quality and quantity of miniaturized parts, fabrication of microparts directly using sheet metals is proven to be promising and efficient for mass production. In this process, however, there are many unknowns in terms of size effect and its affected fracture and deformation behavior. This study is thus aimed at investigating the micromechanical damage and deformation behavior in progressive microforming and establishing a systematic knowledge to support the microformed part design, process configuration and tooling design. In detail, a micro cylindrical part is fabricated via shearing process and a multi-level flanged part is produced via progressive micro extrusion and blanking. To explore the effect of material microstructure on the deformation behavior, ductile fracture and the product quality of microformed part, the original sheet metals are annealed under different temperatures. To realize the microforming process, a progressive microforming system is developed and its characteristics are investigated. The effect of grain size on dimensional accuracy, microstructure evolution and fracture behavior in microforming is also studied. The ductile fracture and its induced defects are identified and the damage accumulation is predicted. In the end, the validity and applicability of different fracture criteria in microforming is discussed.